Pro- and anti-inflammatory cytokines and osteoclastogenesis-related factors in peri-implant diseases: systematic review and meta-analysis - Oliveira, Jovânia Alves; de Oliveira Alves, Roberta; Nascimento, Isabella Mazarelo; Hidalgo, Marco Antonio Rimachi [UNESP]; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Cristina Pigossi, Suzane (Springer Nature, 2023)
Background: Pro- and anti-inflammatory cytokines are acknowledged, during inflammatory bone destruction, as key regulators of osteoclast and osteoblast differentiation and activity. However, evidence regarding the exact role of pro- and anti-inflammatory cytokines and osteoclastogenesis-related factors in peri-implant diseases is unclear. We aimed to execute a systematic review and meta-analysis about the pro- and anti-inflammatory cytokines and osteoclastogenesis-related factors levels in peri-implant diseases. Methods: The focused question was elaborated to summarize the levels of pro-and anti-inflammatory cytokines and osteoclastogenesis-related factors in tissue samples (mRNA) and biofluids (protein levels) of patients with/without peri-implant diseases. Electronic searches of the PubMed, Cochrane Controlled Trials Registry, Web of Science, EMBASE, Scopus and Google scholar databases were conducted for publications up to March 2023. Meta-analysis evaluating the mediator´s levels (protein levels by ELISA) in peri-implant crevicular fluid (PICF) were made. The effect size was estimated and reported as the mean difference. The 95% confidence interval was estimated for each mediator, and the pooled effect was determined significant if two-sided p-values < 0.05 were obtained. Results: Twenty-two publications were included in the systematic review (qualitative analysis), with nine of these subjected to meta-analyses (quantitative analysis). In the qualitative analysis, higher pro-inflammatory cytokines [Interleukin (IL)-1β, IL-6] and pro-osteoclastogenic mediator [Receptor Activator of Nuclear Factor-Kappa B ligand (RANKL)] levels were observed in PICF of individuals with peri-implant diseases in comparison to healthy individuals. Higher RANKL/osteoprotegerin (OPG) ratios were observed in PICF from individuals with peri-implant diseases in comparison to healthy individuals. Meta-analysis showed higher RANKL levels in diseased groups compared to controls. Conclusions: The results showed that the levels of IL-1β, IL-6, IL-10, and RANKL/OPG are not balanced in peri-implant disease, suggesting that these mediators are involved in the host osteo-immunoinflammatory response related to peri-implantitis.
Keywords: Bone resorption; Cytokines; Dental implants; Peri-implantitis